2017
DOI: 10.1515/pjvs-2017-0071
|View full text |Cite
|
Sign up to set email alerts
|

Selection of reference genes for quantitative real-time RT-PCR on gene expression in Golden Pompano (Trachinotus ovatus)

Abstract: Golden pompano (Trachinotus ovatus) is an important economically fish species. In this study, with an aim to identify reliable reference genes for quantitative real-time PCR (qRT-PCR) in golden pompano, we evaluated the expression stability of eight housekeeping genes in the presence and absence of poly I:C stimulation in eight tissues. The PCR data was analyzed by geNorm and NormFinder algorithms. The results showed that the expression of all the examined genes exhibited tissue-dependent variations. When unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 27 publications
(28 reference statements)
0
15
0
Order By: Relevance
“…The ideal reference gene should be stably expressed in all tissues and cell types without being affected by internal or external factors 27 . However, owing to differences in species 45 , 46 , tissue functions 47 , 48 , and metabolic characteristics 49 , 50 , it is almost impossible to obtain universal reference genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ideal reference gene should be stably expressed in all tissues and cell types without being affected by internal or external factors 27 . However, owing to differences in species 45 , 46 , tissue functions 47 , 48 , and metabolic characteristics 49 , 50 , it is almost impossible to obtain universal reference genes.…”
Section: Discussionmentioning
confidence: 99%
“…They are not only involved in protein synthesis, but also in the processes of replication, transcription, RNA processing, DNA repair, self-translational regulation, and developmental regulation. Therefore, these genes can be used as an internal reference genes 47 . The present study showed that the expression levels of RPS29 and RPL19 in different taimen tissues under heat-stress conditions were more stable compared with those of other candidate reference genes.…”
Section: Discussionmentioning
confidence: 99%
“…GAPDH is sensitive to changes in cellular homeostasis, and its expression is modified at tissue level during developmental and physiological conditions (Infante et al, 2008). Unsuitability of GAPDH as RG has been reported in numerous experiments: larval development in Senegalese sole and Atlantic halibut (Infante et al, 2008), bacterial infection in Japanese flounder (Zheng & Sun, 2011), salinity stress in spotted seabass (Wang et al, 2018), developmental stages in zebra fish (McCurley & Callard, 2008) and loach (Chen et al, 2017) and gonadal development in rice eel (Hu et al, 2014). Conversely, some studies have found GAPDH as a stable RG in different embryonic developmental stages of half‐smooth tongue sole (Liu et al, 2014) and magur (Mir et al, 2018), and during myxosporean infection in rainbow trout (Kosakyan et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The ideal reference gene should be stably expressed in all the tissues and cell types without being affected by internal or external factors 13 . However, owing to differences in species 25,26 , tissue functions 27,28 and metabolic characteristics 29,30 , it is almost impossible to obtain universal reference genes. Many researchers optimise the reference genes used for different species.…”
Section: Discussionmentioning
confidence: 99%
“…RPS29, RPL13 and RPL19 encode large ribosomal subunits, and they are highly conserved in eukaryotes. They are not only involved in protein synthesis, but also in the processes of replication, transcription, RNA processing, DNA repair, selftranslational regulation and developmental regulation; therefore, they can be used as an internal reference genes 27 . The present study showed that the expression levels of RPS29 and RPL19 in different taimen tissues under heat-stress conditions were more stable compared with those of other candidate reference genes.…”
Section: Discussionmentioning
confidence: 99%